Effects of cervical rotatory manipulation on the cervical spinal cord complex with ossification of the posterior longitudinal ligament in the vertebral canal: A finite element study - Xue, Fan; Deng, Hao; Chen, Zujiang; Yang, Han; Li, Yikai; Yuan, Shiguo; Zheng, Nansheng; Chen, Meixiong (Frontiers in Bioengineering and Biotechnology, 2023)
Background: There are few studies focusing on biomechanism of spinal cord injury according to the ossification of the posterior longitudinal ligament (OPLL) during cervical rotatory manipulation (CRM). This study aimed to explore the biomechanical effects of CRM on the spinal cord, dura matter and nerve roots with OPLL in the cervical vertebral canal. Methods: Three validated FE models of the craniocervical spine and spinal cord complex were constructed by adding mild, moderate, and severe OPLL to the healthy FE model, respectively. We simulated the static compression of the spinal cord by OPLL and the dynamic compression during CRM in the flexion position. The stress distribution of the spinal cord complex was investigated. Results: The cervical spinal cord experienced higher von Mises stress under static compression by the severe OPLL. A higher von Mises stress was observed on the spinal cord in the moderate and severe OPLL models during CRM. The dura matter and nerve roots had a higher von Mises stress in all three models during CRM. Conclusion: The results show a high risk in performing CRM in the flexion position on patients with OPLL, in that different occupying ratios in the vertebral canal due to OPLL could significantly increase the stress on the spinal cord complex.